Study of the formation mechanism of hierarchical silicon structures produced by sequential ion beam irradiation and anodic etching. (April 2017) - Punzón-Quijorna, Esther; Kajari-Shröder, Sarah; Agulló-Rueda, Fernando; Manso Silván, Miguel; Martín-Palma, Raul José; Herrero Fernández, Pilar; Torres-Costa, Vicente; Climent-Font, Aurelio
Abstract: The formation of micropatterns combining nanostructured (porous) Si (NPSi) and bulk Si is induced by a sequential process of selective high energy ion irradiation and anodic etching. In this work, we investigate the microstructural origin of the increase of Si resistivity on irradiated areas, which is responsible for the inhibition of NPSi formation upon anodization. The increase of Si resistivity after irradiation at variable fluence has been evidenced from current voltage (I-V) characteristics. Microstructural aspects of the Si interfaces irradiated with 1.5–20 MeV Si ions have been revealed by elastic backscattering experiments in channeling configuration, Raman spectroscopy and high resolution transmission electron microscopy. It is concluded that inhibition of NPSi formation is induced at fluences that do not imply amorphization. In fact, the analysis of electrochemical capacitance-voltage measurements suggests that, at fluences well below the threshold for lattice disruption, the concentration of holes suffers from a drastic decrease at depths that match the location of maximum damage yield of the implanted Si ions. These results suggest that the mechanism responsible of formation of hierarchical Si structures is the local B dopant deactivation in the irradiated areas. Highlights: Hierarchical Si structures by subsequent ion irradiation and electrochemical anodization. Gradual Si crystal damage induced by increasing ion fluence. Low fluence irradiation (5.10 13  cm −2 ) readily increases Si resistivity. Maximum concentration of point defects in coincidence with maximum in distribution of implantated ions. Electrochemical evidence of B dopant deactivation at the end of the ion track.